Silica-filled PPO resin-based copper-clad plate and preparation method thereof
By surface treatment of silica and small-molecular polyphenylene ether modification, the mechanical properties and solvent resistance of PPO resin-based copper clad plates are improved, and the shortcomings of pure PPO resin-based copper clad plates in terms of wear resistance, fatigue resistance and strength are solved.
Patent Information
- Application Number
- CN202510138823.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-08
AI Technical Summary
The simple PPO resin-based copper clad plate still needs to improve wear resistance, fatigue resistance and strength, and the compatibility of silica and PPO resin is poor, resulting in a decrease in mechanical properties and insufficient solvent resistance.
By surface treatment of silica, including vinylation and fluorination, it improves its compatibility with PPO resin, and improves the dispersion of silica in the resin by small molecule-multiplexing polyphenylene ether, thereby forming a tighter network structure and improving the mechanical properties and solvent resistance of copper clad plates.
It effectively improves the mechanical properties, thermal stability and solvent resistance of PPO resin-based copper clad plate, and meets higher product requirements.
Smart Images

Figure BDA0005264119900000071 
Figure BDA0005264119900000081 
Figure BDA0005264119900000082
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PPO resin copper clad laminates, in particular to a silicon dioxide-filled PPO resin-based copper clad laminate and a preparation method thereof. Background Art
[0002] With the development of science and technology, the requirements for materials of today's electronic products are getting higher and higher. As the basic material of electronic components, copper clad laminates have a great influence on their performance. PPO resin (polyphenylene ether) has excellent thermal stability and mechanical strength and is widely used in copper clad laminates. However, pure PPO resin-based copper clad laminates still need to continue to improve in terms of wear resistance, fatigue resistance and strength to meet today's product requirements.
[0003] Silicon dioxide is added to PPO resin to improve the performance of copper clad laminates. Silicon dioxide has the advantages of good thermal conductivity, high strength, and low thermal expansion coefficient. Filling it into the PPO resin matrix can effectively improve the mechanical properties, thermal conductivity, fatigue resistance, and wear resistance of copper clad laminates. However, the compatibility between silicon dioxide and PPO resin is poor, resulting in a decrease in the mechanical properties of copper clad laminates, and the solvent resistance of copper clad laminates needs to be improved. Summary of the invention
[0004] The object of the present invention is to provide a silica-filled PPO resin-based copper-clad laminate and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] A PPO resin-based copper-clad laminate filled with silica and a preparation method thereof, comprising the following steps:
[0006] Step 1: (1) reacting silica with acryloyl chloride to obtain vinyl silica; (2) mixing vinyl silica, 5-fluoro-2-mercaptobenzyl alcohol, azobisisobutyronitrile and tetrahydrofuran evenly, reacting at room temperature under ultraviolet light to obtain fluorinated silica; (3) stirring and reacting fluorinated silica with acryloyl chloride in an ice-water bath for 4 to 6 hours to obtain modified silica;
[0007] Step 2: (1) adding polyphenylene ether and tetramethyl bisphenol A to a toluene solution, reacting at 80° C. to 90° C. for 30 to 50 minutes, adding dropwise benzoyl peroxide toluene solution, continuing the reaction for 3 to 5 hours, and purifying to obtain a small molecule polyphenylene ether; (2) reacting the small molecule polyphenylene ether with acryloyl chloride to obtain a modified polyphenylene ether;
[0008] Step 3: uniformly mixing polyphenylene ether, modified polyphenylene ether, modified silica, benzoyl peroxide, and N,N-dimethylformamide to prepare a PPO resin composition prepreg;
[0009] Step 4: Immerse the glass fiber cloth in the PPO resin composition prepreg, roller flattening treatment, and drying to obtain a semi-cured sheet, stack the semi-cured sheets in 5 to 7 layers, cover both sides with copper foil, and press them on a vacuum laminator to obtain a PPO resin-based copper-clad laminate containing 65wt% to 70wt% of the PPO resin composition.
[0010] Furthermore, in step 1 (1), the mass ratio of silicon dioxide to acryloyl chloride is (4-6):1; and the reaction time is 4-6 hours.
[0011] Furthermore, in step 1 (2), the raw material of fluorinated silicon dioxide comprises the following components: by weight, 1 to 3 parts of vinylated silicon dioxide, 5 to 15 parts of 5-fluoro-2-mercaptobenzyl alcohol, 0.05 to 0.1 parts of azobisisobutyronitrile, and 25 to 75 parts of tetrahydrofuran; the conditions for ultraviolet light irradiation are: emission wavelength 350 nm to 365 nm, light intensity 50% to 100%, 80 mW / cm 2 ~100mW / cm 2 , the reaction time is 20 to 30 minutes;
[0012] Furthermore, in step 1 (3), the mass ratio of fluorinated silicon dioxide to acryloyl chloride is (3-5):0.8; and the reaction time is 5-7 hours.
[0013] Furthermore, in step 2 (1), the raw materials of the small molecule polyphenylene ether include the following components: by weight, 15 to 20 parts of polyphenylene ether, 1 to 3 parts of tetramethyl bisphenol A, 0.2 to 0.5 parts of benzoyl peroxide, and 60 to 80 parts of toluene.
[0014] Furthermore, in step 2 (2), the mass ratio of the small molecule polyphenylene ether to acryloyl chloride is (1-3):0.5; and the reaction time is 6-9 hours.
[0015] Furthermore, in the step three, the raw materials of the PPO resin composition prepreg include the following components: by weight, 70 to 100 parts of polyphenylene ether, 20 to 30 parts of modified polyphenylene ether, 10 to 15 parts of modified silica, 0.02 to 0.05 parts of benzoyl peroxide, and 60 to 80 parts of N,N-dimethylformamide.
[0016] Furthermore, in the step 4, the drying temperature is 80°C to 95°C, and the pressing procedure of the vacuum laminator is: temperature is 90°C to 220°C, vacuum degree is 80 bar to 140 bar, and time is 3 to 5 hours.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0018] (1) Silica has a high specific surface area and a unique morphology. Using it as a filler can effectively enhance the strength of PPO resin. Its high specific surface area can effectively absorb and conduct heat, thereby improving the heat resistance of PPO resin. However, the dispersibility of silica in PPO resin is poor. Surface treatment is performed on it to improve the compatibility of silica with PPO resin.
[0019] (2) The hydroxyl groups on the silica react with acryloyl chloride to introduce vinyl groups on its surface, which is then reacted with 5-fluoro-2-mercaptobenzyl alcohol to introduce solvent-resistant fluorinated groups to obtain fluorinated silica. The silica containing fluorinated groups is solvent-resistant, thereby improving the solvent resistance of the copper-clad laminate. The fluorinated silica is further modified to increase its chain length, so that a tighter network structure can be formed with the polyphenylene ether, thereby improving the thermal stability and mechanical properties of the polyphenylene ether resin.
[0020] (3) Reducing the molecular weight of polyphenylene ether can improve the fluidity of silica in the PPO resin composition, thereby improving the mechanical properties and processing properties of the PPO resin. The hydroxyl groups on the small molecular weight polyphenylene ether react with acryloyl chloride to obtain a modified PPO resin, which can improve its compatibility with modified silica. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] In the present embodiment, it should be noted that the following parts are by mass; the purchase manufacturers of all raw materials involved in the present invention are exemplified without any special restrictions: the CAS number of N,N-dimethylformamide is 68-12-2, the CAS number of acryloyl chloride is 814-68-6, the CAS number of azobisisobutyronitrile (AIBN) is 78-67-1, the CAS number of tetrahydrofuran is 109-99-9, the CAS number of 5-fluoro-2-mercaptobenzyl alcohol is 870703-84-7, the CAS number of tetramethyl bisphenol A is 203578-30-7, the CAS number of benzoyl peroxide is 94-36-0, the CAS number of silica purchased is 7631-86-9, and the CAS number of polyphenylene ether (PPO resin) is 31533-76-3.
[0023] Example 1: Step 1: (1) Place silica in a tube furnace and dry at 100° C. for 2 hours, add it to N,N-dimethylformamide, and ultrasonically disperse it at 100 W for 20 minutes to obtain a uniform dispersion; under ice-water bath conditions, add acryloyl chloride dropwise to the dispersion, the mass ratio of silica to acryloyl chloride is 4:1, stir and react for 4 hours, centrifuge and dry the precipitate to obtain vinyl silica; (2) Dissolve vinyl silica and AIBN in tetrahydrofuran, stir and react for 40 minutes, then add 5-fluoro-2-mercaptobenzyl alcohol, mix evenly, and place under ultraviolet light (emission wavelength is 350 nm, light intensity is 50%, 50 mW / cm 2 ) irradiated for 20 minutes, and finally washed and dried to obtain fluorinated silica; the raw materials of fluorinated silica include the following components: 1 part of vinylated silica, 5 parts of 5-fluoro-2-mercaptobenzyl alcohol, 0.05 parts of AIBN, and 25 parts of tetrahydrofuran; (3) adding fluorinated silica to N,N-dimethylformamide, ultrasonically dispersing at a power of 100 W for 20 minutes to obtain a uniform dispersion, adding acryloyl chloride dropwise under ice-water bath conditions, stirring and reacting for 5 hours to obtain modified silica; the mass ratio of fluorinated silica to acryloyl chloride is 3:0.8;
[0024] Step 2: (1) adding polyphenylene ether and tetramethyl bisphenol A to toluene, reacting at 80°C for 30 minutes, adding benzoyl peroxide toluene solution dropwise, continuing the reaction for 3 hours, cooling to room temperature, adding the solution to methanol, with a mass ratio of benzoyl peroxide to methanol of 6:1, rapidly stirring for 40 minutes, filtering, collecting the filtrate, adding the filtrate to methanol and stirring, precipitating solids, filtering, washing and drying to obtain small molecule polyphenylene ether; the raw materials of small molecule polyphenylene ether include the following components: by weight, 15 parts of polyphenylene ether, 1 part of tetramethyl bisphenol A, 0.2 parts of benzoyl peroxide, and 60 parts of toluene; (2) adding small molecule polyphenylene ether to N,N-dimethylformamide, ultrasonically dispersing at 100 W power for 20 minutes, adding acryloyl chloride dropwise in an ice-water bath, stirring for 6 hours, filtering, washing and drying to obtain modified polyphenylene ether; the mass ratio of small molecule polyphenylene ether to acryloyl chloride is 1.7:0.5;
[0025] Step 3: 70 parts of polyphenylene ether, 20 parts of modified polyphenylene ether, 10 parts of modified silica, 0.02 parts of benzoyl peroxide, and 65 parts of N,N-dimethylformamide are uniformly mixed to prepare a PPO resin composition prepreg;
[0026] Step 4: Immerse the glass fiber cloth in the PPO resin composition prepreg, perform roller flattening treatment, and dry at 90°C for 1 hour to obtain a prepreg, stack the prepregs in 4 layers, cover both sides with copper foil, and press on a vacuum laminator to obtain a copper clad laminate with a PPO resin composition content of 65wt%; the pressing procedure is 100°C, 90bar, pressing for 20 minutes; 160°C, 120bar, pressing for 2 hours; 220°C, 140bar, pressing for 2 hours.
[0027] Example 2: Step 1: (1) Place silica in a tube furnace and dry at 100° C. for 2 hours, add it to N,N-dimethylformamide, and ultrasonically disperse it at 100 W for 20 minutes to obtain a uniform dispersion; under ice-water bath conditions, add acryloyl chloride dropwise to the dispersion, the mass ratio of silica to acryloyl chloride is 5:1, stir and react for 5 hours, centrifuge and dry the precipitate to obtain vinyl silica; (2) Dissolve vinyl silica and AIBN in tetrahydrofuran, stir and react for 40 minutes, then add 5-fluoro-2-mercaptobenzyl alcohol, mix evenly, and place under ultraviolet light (emission wavelength is 365 nm, light intensity is 100%, 100 mW / cm 2 ) irradiated for 20 minutes, and finally washed and dried to obtain fluorinated silica; the raw materials of fluorinated silica include the following components: 2 parts of vinylated silica, 10 parts of 5-fluoro-2-mercaptobenzyl alcohol, 0.07 parts of AIBN, and 50 parts of tetrahydrofuran; (3) adding fluorinated silica to N,N-dimethylformamide, ultrasonically dispersing at a power of 100 W for 20 minutes to obtain a uniform dispersion, adding acryloyl chloride dropwise under ice-water bath conditions, stirring and reacting for 5 hours to obtain modified silica. The mass ratio of fluorinated silica to acryloyl chloride is 3.5:0.8;
[0028] Step 2: (1) adding polyphenylene ether and tetramethyl bisphenol A to toluene, reacting at 85°C for 40 minutes, adding benzoyl peroxide toluene solution dropwise, continuing the reaction for 4 hours, cooling to room temperature, adding the solution to methanol, wherein the mass ratio of the solution to methanol is 6:1, rapidly stirring for 40 minutes, filtering, collecting the filtrate, adding the filtrate to methanol and stirring, precipitating solid, filtering, washing and drying to obtain small molecule polyphenylene ether; the raw materials of small molecule polyphenylene ether include the following components: by weight, 17 parts of polyphenylene ether, 1.5 parts of tetramethyl bisphenol A, 0.25 parts of benzoyl peroxide, and 65 parts of toluene; (2) adding small molecule polyphenylene ether to N,N-dimethylformamide, ultrasonically dispersing at 100 W power for 20 minutes, adding acryloyl chloride dropwise in an ice-water bath, stirring for 8 hours, filtering, washing and drying to obtain modified polyphenylene ether; the mass ratio of small molecule polyphenylene ether to acryloyl chloride is 2:0.5;
[0029] Step 3: 85 parts of polyphenylene ether, 20 parts of modified polyphenylene ether, 12 parts of modified silica, 0.03 parts of benzoyl peroxide, and 70 parts of N,N-dimethylformamide are uniformly mixed to form a PPO resin composition prepreg;
[0030] Step 4: Immerse the glass fiber cloth in the PPO resin composition prepreg, roll it flat, and dry it at 95°C for 1 hour to obtain a semi-cured sheet. Stack the semi-cured sheets in 5 layers, cover both sides with copper foil, and press them on a vacuum laminator to obtain a copper-clad laminate with a PPO resin composition content of 68%; the pressing procedure is 100°C, 90 bar, pressing for 20 minutes; 160°C, 120 bar, pressing for 2 hours; 220°C, 140 bar, pressing for 2 hours.
[0031] Example 3: Step 1: (1) Place silica in a tube furnace and dry at 100° C. for 2 hours, add it to N,N-dimethylformamide, and ultrasonically disperse it at 100 W for 20 minutes to obtain a uniform dispersion; under ice-water bath conditions, add acryloyl chloride dropwise to the dispersion, the mass ratio of silica to acryloyl chloride is 6:1, stir and react for 6 hours, centrifuge and dry the precipitate to obtain vinyl silica; (2) Dissolve vinyl silica and AIBN in tetrahydrofuran, stir and react for 40 minutes, then add 5-fluoro-2-mercaptobenzyl alcohol, mix evenly, and place under ultraviolet light (emission wavelength is 365 nm, light intensity is 80%, 80 mW / cm 2 ) irradiated for 20 minutes, and finally washed and dried to obtain fluorinated silica; the raw materials of fluorinated silica include the following components: 2.5 parts of vinylated silica, 12 parts of 5-fluoro-2-mercaptobenzyl alcohol, 0.1 parts of AIBN, and 60 parts of tetrahydrofuran; (3) adding fluorinated silica to N,N-dimethylformamide, ultrasonically dispersing at a power of 100 W for 20 minutes to obtain a uniform dispersion, adding acryloyl chloride dropwise under ice-water bath conditions, stirring and reacting for 7 hours to obtain modified silica. The mass ratio of fluorinated silica to acryloyl chloride is 4.5:0.8;
[0032] Step 2: (1) adding polyphenylene ether and tetramethyl bisphenol A to toluene, reacting at 90° C. for 45 minutes, adding dropwise benzoyl peroxide toluene solution, continuing the reaction for 5 hours, cooling to room temperature, adding the solution to methanol, wherein the mass ratio of the solution to methanol is 6:1, rapidly stirring for 40 minutes, filtering, collecting the filtrate, adding the filtrate to methanol and stirring, precipitating solid, filtering, washing and drying to obtain small molecule polyphenylene ether; the raw materials of small molecule polyphenylene ether include the following components: by weight, 20 parts of polyphenylene ether, 2 parts of tetramethyl bisphenol A, 0.3 parts of benzoyl peroxide, and 70 parts of toluene; (3) adding small molecule polyphenylene ether to N,N-dimethylformamide, ultrasonically dispersing at 100 W power for 20 minutes, adding dropwise acryloyl chloride in an ice-water bath, stirring for 9 hours, filtering, washing and drying to obtain modified polyphenylene ether; the mass ratio of small molecule polyphenylene ether to acryloyl chloride is 3:0.5;
[0033] Step 3: 90 parts of polyphenylene ether, 20 parts of modified polyphenylene ether, 15 parts of modified silica, 0.04 parts of benzoyl peroxide, and 80 parts of N,N-dimethylformamide are uniformly mixed to form a PPO resin composition prepreg;
[0034] Step 4: Immerse the glass fiber cloth in the PPO resin composition prepreg, roll it flat, dry it at 95°C for 1 hour to obtain a semi-cured sheet, stack the semi-cured sheets in 6 layers, cover both sides with copper foil, and press them on a vacuum laminator to obtain a copper-clad laminate with a PPO resin composition content of 70%; the pressing procedure is 100°C, 90 bar for 20 minutes; 160°C, 120 bar for 2 hours; 220°C, 140 bar for 2 hours.
[0035] Comparative Example 1: Step 1: (1) Place silica in a tube furnace and dry at 100° C. for 2 hours, add it to N,N-dimethylformamide, and ultrasonically disperse it at 100 W for 20 minutes to obtain a uniform dispersion; under ice-water bath conditions, add acryloyl chloride dropwise to the dispersion, the mass ratio of silica to acryloyl chloride is 5:1, stir and react for 5 hours, and dry the precipitate after centrifugation to obtain vinyl silica; (2) Dissolve vinyl silica and AIBN in tetrahydrofuran, stir and react for 40 minutes, then add 5-fluoro-2-mercaptobenzyl alcohol, mix evenly, and place under ultraviolet light (emission wavelength is 365 nm, light intensity is 100%, 100 mW / cm 2) irradiated for 20 minutes, and finally washed and dried to obtain fluorinated silica; the raw materials of fluorinated silica include the following components: 2 parts of vinylated silica, 10 parts of 5-fluoro-2-mercaptobenzyl alcohol, 0.07 parts of AIBN, and 50 parts of tetrahydrofuran; (3) adding fluorinated silica to N,N-dimethylformamide, ultrasonically dispersing at a power of 100 W for 20 minutes to obtain a uniform dispersion, adding acryloyl chloride dropwise under ice-water bath conditions, stirring and reacting for 5 hours to obtain modified silica; the mass ratio of fluorinated silica to acryloyl chloride is 3.5:0.8;
[0036] Step 2: (1) adding polyphenylene ether and tetramethyl bisphenol A to toluene, reacting at 85° C. for 40 minutes, adding dropwise a benzoyl peroxide toluene solution, continuing the reaction for 4 hours, cooling to room temperature, adding the solution to methanol at a mass ratio of 6:1 to methanol, rapidly stirring for 40 minutes, filtering, collecting the filtrate, adding the filtrate to methanol and stirring, precipitating a solid, filtering, washing and drying to obtain a small molecule polyphenylene ether; the raw materials of the small molecule polyphenylene ether include the following components: by weight, 17 parts of polyphenylene ether, 1.5 parts of tetramethyl bisphenol A, 0.25 parts of benzoyl peroxide, and 65 parts of toluene;
[0037] Step 3: 85 parts of polyphenylene ether, 20 parts of modified polyphenylene ether, 12 parts of modified silica, 0.03 parts of benzoyl peroxide, and 70 parts of N,N-dimethylformamide are uniformly mixed to form a PPO resin composition prepreg;
[0038] Step 4: Dip the glass fiber cloth in the PPO resin composition prepreg, roll it flat, dry it at 95°C for 1 hour to obtain a prepreg, stack the prepregs in 5 layers, cover both sides with copper foil, and press them on a vacuum laminator to obtain a copper clad laminate with a PPO resin composition content of 68%; the pressing procedure is 100°C, 90 bar for 20 minutes; 160°C, 120 bar for 2 hours; 220°C, 140 bar for 2 hours;
[0039] Comparative Example 1 is based on Example 2, but the small molecule polyphenylene ether is not modified.
[0040] Comparative Example 2: Step 1: (1) placing silica in a tube furnace and drying it at 100° C. for 2 hours, adding it to N,N-dimethylformamide, and ultrasonically dispersing it at a power of 100 W for 20 minutes to obtain a uniform dispersion; under ice-water bath conditions, adding acryloyl chloride dropwise to the dispersion, the mass ratio of silica to acryloyl chloride being 5:1, stirring and reacting for 5 hours, and drying the precipitate after centrifugation to obtain vinylated silica;
[0041] Step 2: (1) adding polyphenylene ether and tetramethyl bisphenol A to toluene, reacting at 85°C for 40 minutes, adding benzoyl peroxide toluene solution dropwise, continuing the reaction for 4 hours, cooling to room temperature, adding the solution to methanol, the mass ratio of which to methanol is 6:1, rapidly stirring for 40 minutes, filtering, collecting the filtrate, adding the filtrate to methanol and stirring, precipitating solids, filtering, washing and drying to obtain small molecule polyphenylene ether; the raw materials of small molecule polyphenylene ether include the following components: by weight, 17 parts of polyphenylene ether, 1.5 parts of tetramethyl bisphenol A, 0.25 parts of benzoyl peroxide, and 65 parts of toluene; (3) adding small molecule polyphenylene ether to N,N-dimethylformamide, ultrasonically dispersing at 100 W power for 20 minutes, adding acryloyl chloride dropwise in an ice-water bath, stirring for 8 hours, filtering, washing and drying to obtain modified polyphenylene ether; the mass ratio of small molecule polyphenylene ether to acryloyl chloride is 2:0.5;
[0042] Step 3: 85 parts of polyphenylene ether, 20 parts of modified polyphenylene ether, 12 parts of modified silica, 0.03 parts of benzoyl peroxide, and 70 parts of N,N-dimethylformamide are uniformly mixed to form a PPO resin composition prepreg;
[0043] Step 4: Dip the glass fiber cloth in the PPO resin composition prepreg, roll it flat, dry it at 95°C for 1 hour to obtain a prepreg, stack the prepregs in 5 layers, cover both sides with copper foil, and press them on a vacuum laminator to obtain a copper clad laminate with a PPO resin composition content of 68%; the pressing procedure is 100°C, 90 bar for 20 minutes; 160°C, 120 bar for 2 hours; 220°C, 140 bar for 2 hours;
[0044] Comparative Example 2 is based on Example 2, except that the modified silica is replaced by vinyl silica.
[0045] Comparative Example 3: Step 1: (1) Place silica in a tube furnace and dry at 100° C. for 2 hours, add it to N,N-dimethylformamide, and ultrasonically disperse it at 100 W for 20 minutes to obtain a uniform dispersion; under ice-water bath conditions, add acryloyl chloride dropwise to the dispersion, the mass ratio of silica to acryloyl chloride is 5:1, stir and react for 5 hours, centrifuge and dry the precipitate to obtain vinyl silica; (2) Dissolve vinyl silica and AIBN in tetrahydrofuran, stir and react for 40 minutes, then add 5-fluoro-2-mercaptobenzyl alcohol, mix evenly, and place under ultraviolet light (emission wavelength is 365 nm, light intensity is 100%, 100 mW / cm 2) irradiated for 20 minutes, and finally washed and dried to obtain fluorinated silica; the raw materials of fluorinated silica include the following components: 2 parts of vinylated silica, 10 parts of 5-fluoro-2-mercaptobenzyl alcohol, 0.07 parts of AIBN, and 50 parts of tetrahydrofuran; (3) adding fluorinated silica to N,N-dimethylformamide, ultrasonically dispersing at a power of 100 W for 20 minutes to obtain a uniform dispersion, adding acryloyl chloride dropwise under ice-water bath conditions, stirring and reacting for 5 hours to obtain modified silica; the mass ratio of fluorinated silica to acryloyl chloride is 3.5:0.8;
[0046] Step 3: 85 parts of polyphenylene ether, 12 parts of modified silica, 0.03 parts of benzoyl peroxide, and 70 parts of N,N-dimethylformamide are uniformly mixed to form a PPO resin composition prepreg;
[0047] Step 4: Dip the glass fiber cloth in the PPO resin composition prepreg, roll it flat, dry it at 95°C for 1 hour to obtain a prepreg, stack the prepregs in 5 layers, cover both sides with copper foil, and press them on a vacuum laminator to obtain a copper clad laminate with a PPO resin composition content of 68%; the pressing procedure is 100°C, 90 bar for 20 minutes; 160°C, 120 bar for 2 hours; 220°C, 140 bar for 2 hours;
[0048] Comparative Example 3 is based on Example 2, but without adding modified polyphenylene ether.
[0049] Test experiment 1: According to GB / T2571-1981 standard and GB / T2571-1995 standard, the samples of Examples 1 to 3 and Comparative Examples 1 to 3 were tested respectively. At room temperature, the impact rate of the impact strength was 2.9 m / s, and the loading rate of the bending strength was 2 mm / min.
[0050]
[0051]
[0052] Table 1
[0053] Test 2: Solvent resistance test: The copper clad laminates of Example 2 and Comparative Examples 1 to 3 were cut into 80 mm × 50 mm × 4 mm according to GB / T6968-2011 standard. Calculate the mass change rate of the copper clad laminate immersed in toluene: The copper clad laminates of Examples 1 to 3 and Comparative Examples 1 to 3 were weighed and recorded as M. 1 After weighing, the sample was immersed in toluene for 5, 40, and 160 hours. At the corresponding time point, the sample was taken out, dried, and weighed, which was recorded as m 2 , and according to the formula (M 1 -m 2 ) / M 1×100%, and the mass change rate is calculated; the test data is shown in Table 1.
[0054]
[0055] Conclusion: Comparative Example 1 is based on Example 2, and the small molecule polyphenylene ether is not modified, resulting in a decrease in the dispersibility of the modified silica in the PPO resin, thereby reducing the impact strength and flexural strength of the copper clad laminate. It can be seen from Table 2 that the solvent resistance of Comparative Example 1 is lower than that of Example 2. Comparative Example 2 is based on Example 2, and the modified silica is changed to vinylized silica. The vinyl group on the silica can modify the hydroxyl group on the polyphenylene ether, but the reaction is slow, resulting in lower impact resistance and flexural strength of Comparative Example 2 than in Example 2, but because the fluorinated group is not introduced, its mass change rate increases with time, resulting in a decrease in its solvent resistance. Comparative Example 3 is based on Example 2, and no modified polyphenylene ether is added, resulting in a decrease in the compatibility of polyphenylene ether with modified silica, so that the silica containing fluorine groups is unevenly distributed in the polyphenylene ether, which ultimately leads to a decrease in the impact strength and flexural strength of the copper clad laminate and a decrease in solvent resistance.
[0056] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a PPO resin-based copper-clad laminate filled with silica, characterized in that: The following steps are involved: S1: (1) reacting silica with acryloyl chloride in an ice-water bath to obtain vinyl silica; (2) mixing vinyl silica, 5-fluoro-2-mercaptobenzyl alcohol, azobisisobutyronitrile and tetrahydrofuran evenly, and reacting at room temperature under ultraviolet light to obtain fluorinated silica; (3) reacting fluorinated silica with acryloyl chloride in an ice-water bath again to obtain modified silica; S2: (1) adding polyphenylene ether and tetramethyl bisphenol A to a toluene solution, stirring at 80°C to 90°C for 30 to 50 minutes, adding dropwise benzoyl peroxide toluene solution, continuing the reaction for 3 to 5 hours, and purifying to obtain a small molecule polyphenylene ether; (2) reacting the small molecule polyphenylene ether with acryloyl chloride to obtain a modified polyphenylene ether; S3: uniformly mixing polyphenylene ether, modified polyphenylene ether, modified silica, benzoyl peroxide, and N,N-dimethylformamide to prepare a PPO resin composition prepreg; S4: Immerse the glass fiber cloth in the PPO resin composition prepreg, perform roller flattening treatment, and dry to obtain a semi-cured sheet; stack the semi-cured sheets in 5 to 7 layers, cover both sides with copper foil, and press them on a vacuum laminator to obtain a PPO resin-based copper-clad laminate containing 65wt% to 70wt% of the PPO resin composition.
2. The method for preparing a silica-filled PPO resin-based copper-clad laminate according to claim 1, characterized in that: In S1(1), the mass ratio of silicon dioxide to acryloyl chloride is (4-6):1, and the reaction time is 4-6 hours.
3. The method for preparing a silica-filled PPO resin-based copper-clad laminate according to claim 1, characterized in that: In S1(2), the raw materials of fluorinated silicon dioxide include the following components: by weight, 1 to 3 parts of vinylated silicon dioxide, 5 to 15 parts of 5-fluoro-2-mercaptobenzyl alcohol, 0.05 to 0.1 parts of azobisisobutyronitrile, and 25 to 75 parts of tetrahydrofuran; the conditions for ultraviolet light irradiation are: emission wavelength 350 nm to 365 nm, light intensity 50% to 100%, 80 mW / cm 2 ~100mW / cm 2 , the reaction time is 20 to 30 minutes.
4. The method for preparing a silica-filled PPO resin-based copper-clad laminate according to claim 1, characterized in that: In S1(3), the mass ratio of fluorinated silicon dioxide to acryloyl chloride is (3-5):0.8; and the reaction time is 5-7 hours.
5. The method for preparing a silica-filled PPO resin-based copper-clad laminate according to claim 1, characterized in that: In S2(1), the raw materials of the small molecule polyphenylene ether include the following components: by weight, 15 to 20 parts of polyphenylene ether, 1 to 3 parts of tetramethyl bisphenol A, 0.2 to 0.5 parts of benzoyl peroxide, and 60 to 80 parts of toluene.
6. The method for preparing a silica-filled PPO resin-based copper-clad laminate according to claim 1, characterized in that: In S2(2), the mass ratio of small molecule polyphenylene ether to acryloyl chloride is (1-3):0.5; and the reaction time is 6-9 hours.
7. The method for preparing a silica-filled PPO resin-based copper-clad laminate according to claim 1, characterized in that: In S3, the raw materials of the PPO resin composition prepreg include the following components: by weight, 70 to 100 parts of polyphenylene ether, 20 to 30 parts of modified polyphenylene ether, 10 to 15 parts of modified silica, 0.02 to 0.05 parts of benzoyl peroxide, and 60 to 90 parts of N,N-dimethylformamide.
8. The method for preparing a silica-filled PPO resin-based copper-clad laminate according to claim 1, characterized in that: In S4, the drying temperature is 80°C to 95°C, and the pressing procedure of the vacuum laminator is: temperature is 90°C to 220°C, vacuum degree is 80 bar to 140 bar, and time is 3 to 5 hours. 9 . A copper-clad laminate prepared according to the method for preparing a silica-filled PPO resin-based copper-clad laminate according to any one of claims 1 to 8 .
Citation Information
Patent Citations
Super hydrophobic silicon-fluorine polymer / nanometer silica hybridization nanometer material and preparation method thereof
CN101805434A
UV-resistant superhydrophobic coating compositions
CN106574173A
Polyphenylene oxide resin for copper-clad plates
CN107163244A
PPO resin-based copper-clad plate with low dielectric loss and preparation method thereof
CN116080211A
Preparation method of super-hydrophobic self-cleaning aluminum alloy coating
CN116218320A